2013
DOI: 10.1111/tmi.12183
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug‐resistant TB in Zambia: review of national data from 2000 to 2011

Abstract: Abstractbackground Multidrug-resistant tuberculosis (MDR-TB) is posing a great threat to global TB control. The burden in Zambia is not well defined because routine surveillance data are scarce. We reviewed national MDR-TB data for the last decade to inform future public health policy with respect to MDR-TB in Zambia.method Retrospective review of national surveillance of MDR-TB data, TB programme and laboratory reports between 2000 and 2011.results The total number of DSTs performed during this 11-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In this study we showed that GeneXpert identified 9 (5.9%) cases of rifampicin resistant TB out of the total (152) cases of TB in the year 2015 at Livingstone Central Hospital (LCH). The prevalence of rifampicin resistance in the current study is consistent with other published studies [ 12 , 13 ]. However, a much lower and higher proportion was found in a study which was conducted in India [ 14 ] and in Ghana [ 3 ], respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study we showed that GeneXpert identified 9 (5.9%) cases of rifampicin resistant TB out of the total (152) cases of TB in the year 2015 at Livingstone Central Hospital (LCH). The prevalence of rifampicin resistance in the current study is consistent with other published studies [ 12 , 13 ]. However, a much lower and higher proportion was found in a study which was conducted in India [ 14 ] and in Ghana [ 3 ], respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The case of MDR-TB and co-infection with HIV may need further investigation as the cases of HIV negative participants were very few (2) in the sample population under our study. A study conducted in Zambia [ 13 ] that reviewed records from 2000 to 2011 found no data available on MDR-TB / HIV co-infections and this was attributed to inadequate reporting and recording.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, a national survey of drug resistance was carried out following the WHO recommended methodology of clustered sampling and culture on Löwenstein Jensen (LJ) medium . Prevalence of multidrug resistance TB was estimated to be 1.8% (95% CI 0.8–3.5) in a nationally representative sample of smear‐positive tuberculosis patients including both new and retreatment cases in 2001 .…”
Section: Introductionmentioning
confidence: 99%
“…The region also has high rates of HIV prevalence and consequently high TB/HIV co-infection rates (WHO 2015; Kapata et al 2011). In 2015, WHO estimated that 480,000 people developed MDR-TB but only 26% of these were notified, even fewer were started on treatment and the treatment outcomes were poor with less than half of these Research Centre in Ndola (Kapata et al 2013). However, only a few patients were started on second line treatment at two hospital facilities in the country.…”
Section: ; Lukoye Et Al 2015)mentioning
confidence: 99%